Dinamika Pendidikan Islam di Indonesia: Kajian Historis Dari Tradisional Menuju Kontemporer - Mohammad Asrori (UIN Maulana Malik Ibrahim Malang, 2008)
Observing Islamic education in Indonesia, historically, it was started from a religious boarding school called